(untitled) (KULT_online, 2020)
From the beginning of the 21st century, world literature has been a resurgent concept and a highly influential field. But it has also been relatively weak and uniform on literary theory, as well as susceptible to perpetuating an old world order. On both counts, Lorna Burns’s Postcolonialism after World Literature: Relation, Equality, Dissent offers a major intervention and essential reading for anyone interested in global and postcolonial trajectories of literature today. Engaging theorists in discourse – from Bruno Latour and Rita Felski to Gilles Deleuze, Édouard Glissant, and ultimately Jacques Rancière – as well as writers like J. M. Coetzee, Arundhati Roy, and Kamila Shamsie, the book assembles new philosophical and post-critical perspectives for conjoining postcolonial and world literary studies.